Linguistic and communicative aspects of argumentation in the business field of communication - Maira Zhunissova, Karlygash Shokhayeva,; Orynkhanova, Gibadat; Zhunissova, Jadira (Opción, 2020)
The article deals with the pragmatic aspects of argumentation in business communication. It is argued that a persuasive speech is a very important competence of specialists in business communication. Only directly negotiating, providing evidences, arguments, counter-arguments, and controversy the negotiators can move quickly to the overall objective of the agreement. Even with a well-developed modern means of communication, the Internet, electronic argumentation support systems, specialists in business communication. In bargaining process negotiator demonstrates himself, his appearance, mind, manners, emotions, ethics, etiquette knowledge, characteristics of voice, gestures, movements, facial expressions, reactions and his language - communication options.